HYPERTENSION AND BLOOD PRESSURE CONTROL AMONG RESPONDENTS LIVING IN DHAKA DIVISION, BANGLADESH. (April 2021) - Hasan, Mehedi; Khan, Md Showkat Ali; Sutradhar, Ipsita; Hossaine, Moyazzam; Yoshimura, Yukie; Choudhury, Sohel Reza; Sarker, Malabika; Mridha, Malay Kanti
Abstract : Objective: In Bangladesh, 67% of all deaths are due to non-communicable diseases (NCDs), of which17% are attributable to cardiovascular diseases (CVD). Hypertension is a major risk factor for CVD. We conducted a baseline survey titled SHASTO (Strengthening Health Systems through Organizing Communities) to estimate the prevalence of hypertension, their risk factors, health care seeking behaviour among residents living in Dhaka division of Bangladesh. Design and method: This cross-sectional study was conducted among residents aged >30 years living in Dhaka north, Dhaka south, Narsinghdi and Gazipur district of Dhaka division. The respondents were interviewed using a modified version of STEPS questionnaire and physical measurements were taken following a standard operating procedure. Hypertension was defined as systolic blood pressure (BP) > = 140 mm of Hg and/or diastolic BP > = 90 mm of Hg and/or persons with already diagnosed hypertension. Results: A total of 4930 respondents participated in the study and mean age of male and female respondents was 48 and 45 years respectively. Overall, 31% of the respondents were hypertensive and the prevalence was higher among urban (37%) and female (38%) respondents than their rural (31%) and male (24%) counterparts. A higher prevalence of hypertension was also observed among respondents currently not working (not working: 47% vs working: 30%), consumed inadequate fruits and vegetables (inadequate: 32% vs adequate: 28%), performed inadequate physical activities (inadequate: 43% vs adequate: 28%) and overweight or obese (overweight/obese: 39% vs not overweight/obese: 24%). About 75% of hypertensive patients were aware of their status and 64% of them sought care. More than half (54%) of them were taking medication, however, 44% of them had uncontrolled BP. The prevalence of uncontrolled BP was found higher among female (63%), rural (89%), overweight or obese (60%), and nuclear family (63%) respondents. Conclusions: The prevalence of hypertension and uncontrolled BP was high among respondents living in Dhaka division of Bangladesh. The government should implement hypertension control and prevention programmes to tackle the burden and its associated complications.